Impact of individual IEQ factors on passengers' overall satisfaction in Chinese airport terminals. (1st February 2017) - Geng, Yang; Yu, Juan; Lin, Borong; Wang, Zhe; Huang, Yenhsiang
Abstract: In this paper, objective environmental measurements and subjective questionnaire surveys are conducted in 8 major Chinese airport terminals to investigate Indoor environment quality (IEQ) and explore the relationship between individual IEQ factors and overall satisfaction. The objective measurements show that the qualification rate of indoor thermal environment is above 70%, according to Chinese thermal standard; the average CO2 concentration is controlled between 350 PPM and 700 PPM; the average value of natural light illuminance ranges from 300 lx to 500 lx; and the noise intensity stays at a high level, whose average value is between 55 dB(A) and 70 dB(A). The analysis of subjective surveys finds the majority of passengers are just satisfied with IEQ in the airport terminals. It is also found that the subjective satisfactory level is highly correlated with the objective environmental measurement. Based on Kano's model, the impacts of individual IEQ factors on overall satisfaction are analyzed. The results indicate 'Thermal Comfort' and 'Space Layout' areBasic Factors, which have prominently negative influences on passengers' overall satisfaction when they are underperformed. Conversely, 'Service Facility' isBonus Factor, which means a greater positive effect on overall satisfaction if it performs well. In addition, 'Acoustic Quality', 'Air Quality' and 'Lighting' areProportional Factors, whose impact on overall satisfaction is in linear proportion to its performance. Highlights: IEQ in eight Chinese airport terminals has been investigated. The physical parameters of four main IEQ factors are measured in the long term. 3489 subjects voted in six IEQ factors and overall satisfaction. The subjective satisfaction is highly correlated with the objective measurement. IEQ factors have different impacts on overall satisfaction, according to Kano's model.